STRATEGI PENGELOLAAN WAKAF PRODUKTIF DALAM RANGKA PEMBERDAYAAN UMAT DI KECAMATAN PANGKAJENE KABUPATEN PANGKEP - Azis, Ishan (Institut Agama Islam Negeri (IAIN) Ternate, 2021)
This study aims to determine the management strategy of productive waqf in the context of empowering people in Pangkajene District, Pangkep Regency. This study uses field research with a descriptive qualitative approach. The research location is centered in Pangkep Regency, Pangkajene District, South Sulawesi. The data used are primary data directly from those who manage productive waqf in Pangkep and secondary data from reference books, journals and so on. Data collection techniques ranging from interviews, observation and documentation. The management of productive waqf in Pangkajene District in its implementation is in accordance with Law Number 41 of 2004 concerning waqf but in the management of productive waqf it is still not optimal. In the management of productive waqf property as waqf by the wakif, so far the KUA of Pangkajene Sub-district has never interfered with all management affairs entirely left to the nadzir who has been appointed by the wakif himself. Productive waqf in Pangkajene District is classified as absolute waqf practice, Nazhir makes productive efforts so that waqf assets can be maximized in a way that is mostly achieved by renting out waqf assets.